Evaluating Oil Price Movement and Revenue Generation in Nigeria during Covid-19 Pandemic: Experience from Pre and Post Era - Manasseh, Charles O.; Nwonye, Nnenna G.; Abada, Felicia C.; Okanya, Ogochukwu; Ogbuagu, Anuli R.; Eze-Dike, Felicia U.; Okonkwo, Osmond N.; Samson, Otene; Akamike, Okechukwu J.; Okoh, John O.; et al. (International Journal of Energy Economics and Policy, 2022)
The study focusses on evaluating oil price movement and revenue generation in Nigeria with emphasis on the era of pre and post covid-19 pandemic. Measures such as crude oil price, domestic production, crude oil export and revenue, and revenue generation were assessed before, during and after covid-19 pandemic. The evidence shows that oil price and revenue generation were negatively affected during covid-19 pandemic era due to restriction on the movement of people and economic activities. Hence, the study further revealed a drastic fall in crude oil price and export, as well as domestic production (mbd) especially during the first quarter of 2020. While crude oil price appreciated slightly from June, the export and domestic production plummeted with a corresponding decrease in revenue generation which dropped deeply from 47 billion USD in 2019 to 8 billion USD in 2020. Further evaluation revealed that after the introduction of some measures by the government authorities, the Nigerian economic start to recover, which results to a slight improvement in crude oil price in December 2020, but later fell to 40.28 mbd in march 2021. Thus, other indicators such as domestic production and crude oil export has no sign of recovery between this period except for revenue generation which increases by 4 billion USD. Moreso, to control the aftermath of pandemic, we suggest for cohesive policy measures such as educating people on the benefits of covid-19 vaccines and proper enforcement on the use of facemask. In turn, this will reduce the spread and promote economic activities in Nigeria. In addition, policies that could regulate oil price movement should be initiated. Consequently, it may likely encourage increase in revenue generation in Nigeria.